If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6/x-5+6/5x-25=2
We move all terms to the left:
6/x-5+6/5x-25-(2)=0
Domain of the equation: x!=0
x∈R
Domain of the equation: 5x!=0We add all the numbers together, and all the variables
x!=0/5
x!=0
x∈R
6/x+6/5x-32=0
We calculate fractions
30x/5x^2+6x/5x^2-32=0
We multiply all the terms by the denominator
30x+6x-32*5x^2=0
We add all the numbers together, and all the variables
36x-32*5x^2=0
Wy multiply elements
-160x^2+36x=0
a = -160; b = 36; c = 0;
Δ = b2-4ac
Δ = 362-4·(-160)·0
Δ = 1296
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{1296}=36$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(36)-36}{2*-160}=\frac{-72}{-320} =9/40 $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(36)+36}{2*-160}=\frac{0}{-320} =0 $
| 3(2x-2)-5(3x+5)=-4x-144 | | 7x+6/10+9x-8/4=-25 | | 5l-3=21+18 | | 8x-36=4x+6 | | 3x+4+1.1-0.1=-21 | | 9(x+13)=16x-4 | | 2x+14=4x−16 | | 16x+2=106+3x | | 6-2(-5x-6)=-7+3(x-1) | | 5x+7=2x+16x= | | 26x-10=166+4x | | 5d–1=9 | | 6x+8/2+8x-1/7=-21 | | X(2x-10)=12 | | 8x-2=54+1x | | -6-3(4x-2)=x-39 | | a+3=4a-9 | | 8/x+5=-24/x+1 | | 8x+5=23-1x | | x-4=-6x+3 | | 17x-7=50-2x | | 3x-5=5+5x | | 7c=10c | | -3(x+2)-5=16 | | 3b–4=17b= | | 6x-3=14-5x | | 9/x+5=-3/x-3 | | 7−11x=−14 | | x-1=2x-5=1 | | 3w=60 | | 4(x-6)+7x=8(x+5) | | 1/3m-2=-6 |